At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Explore thousands of questions and answers from knowledgeable experts in various fields on our Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Certainly! Let's go through each part step by step to find the required results.
### a. [tex]\( (-30) \div 10 \)[/tex]
To solve [tex]\( (-30) \div 10 \)[/tex]:
- Dividing a negative number by a positive number gives a negative result.
- [tex]\( \frac{-30}{10} = -3 \)[/tex]
So, [tex]\( (-30) \div 10 = -3.0 \)[/tex]
### b. [tex]\( (-49) \div 49 \)[/tex]
To solve [tex]\( (-49) \div 49 \)[/tex]:
- Dividing a negative number by a positive number gives a negative result.
- [tex]\( \frac{-49}{49} = -1 \)[/tex]
So, [tex]\( (-49) \div 49 = -1.0 \)[/tex]
### c. [tex]\( 50 \div (-5) \)[/tex]
To solve [tex]\( 50 \div (-5) \)[/tex]:
- Dividing a positive number by a negative number gives a negative result.
- [tex]\( \frac{50}{-5} = -10 \)[/tex]
So, [tex]\( 50 \div (-5) = -10.0 \)[/tex]
### d. [tex]\( 13 \div (-2 + 1) \)[/tex]
To solve [tex]\( 13 \div (-2 + 1) \)[/tex]:
- First, solve the expression in the denominator, [tex]\((-2 + 1)\)[/tex].
[tex]\( -2 + 1 = -1 \)[/tex]
- Dividing by a negative number gives a negative result.
- [tex]\( \frac{13}{-1} = -13 \)[/tex]
So, [tex]\( 13 \div (-2 + 1) = -13.0 \)[/tex]
### e. [tex]\( (-36) \div (-9) \)[/tex]
To solve [tex]\( (-36) \div (-9) \)[/tex]:
- Dividing a negative number by a negative number gives a positive result.
- [tex]\( \frac{-36}{-9} = 4 \)[/tex]
So, [tex]\( (-36) \div (-9) = 4.0 \)[/tex]
### f. [tex]\( -36 \div 12 \)[/tex]
To solve [tex]\( -36 \div 12 \)[/tex]:
- Dividing a negative number by a positive number gives a negative result.
- [tex]\( \frac{-36}{12} = -3 \)[/tex]
So, [tex]\( -36 \div 12 = -3.0 \)[/tex]
### g. [tex]\( 0 \div (-12) \)[/tex]
To solve [tex]\( 0 \div (-12) \)[/tex]:
- Dividing zero by any non-zero number always gives zero.
- [tex]\( \frac{0}{-12} = 0 \)[/tex]
So, [tex]\( 0 \div (-12) = -0.0 \)[/tex]
### h. [tex]\( (-6 + 3) \div (-2 + 1) \)[/tex]
To solve [tex]\( (-6 + 3) \div (-2 + 1) \)[/tex]:
- First, solve the expressions inside the parentheses.
[tex]\( -6 + 3 = -3 \)[/tex] and [tex]\( -2 + 1 = -1 \)[/tex]
- Next, divide [tex]\( -3 \)[/tex] by [tex]\( -1 \)[/tex].
- Dividing a negative number by a negative number gives a positive result.
- [tex]\( \frac{-3}{-1} = 3 \)[/tex]
So, [tex]\( (-6 + 3) \div (-2 + 1) = 3.0 \)[/tex]
In summary:
- [tex]\( (-30) \div 10 = -3.0 \)[/tex]
- [tex]\( (-49) \div 49 = -1.0 \)[/tex]
- [tex]\( 50 \div (-5) = -10.0 \)[/tex]
- [tex]\( 13 \div (-2 + 1) = -13.0 \)[/tex]
- [tex]\( (-36) \div (-9) = 4.0 \)[/tex]
- [tex]\( -36 \div 12 = -3.0 \)[/tex]
- [tex]\( 0 \div (-12) = -0.0 \)[/tex]
- [tex]\( (-6 + 3) \div (-2 + 1) = 3.0 \)[/tex]
### a. [tex]\( (-30) \div 10 \)[/tex]
To solve [tex]\( (-30) \div 10 \)[/tex]:
- Dividing a negative number by a positive number gives a negative result.
- [tex]\( \frac{-30}{10} = -3 \)[/tex]
So, [tex]\( (-30) \div 10 = -3.0 \)[/tex]
### b. [tex]\( (-49) \div 49 \)[/tex]
To solve [tex]\( (-49) \div 49 \)[/tex]:
- Dividing a negative number by a positive number gives a negative result.
- [tex]\( \frac{-49}{49} = -1 \)[/tex]
So, [tex]\( (-49) \div 49 = -1.0 \)[/tex]
### c. [tex]\( 50 \div (-5) \)[/tex]
To solve [tex]\( 50 \div (-5) \)[/tex]:
- Dividing a positive number by a negative number gives a negative result.
- [tex]\( \frac{50}{-5} = -10 \)[/tex]
So, [tex]\( 50 \div (-5) = -10.0 \)[/tex]
### d. [tex]\( 13 \div (-2 + 1) \)[/tex]
To solve [tex]\( 13 \div (-2 + 1) \)[/tex]:
- First, solve the expression in the denominator, [tex]\((-2 + 1)\)[/tex].
[tex]\( -2 + 1 = -1 \)[/tex]
- Dividing by a negative number gives a negative result.
- [tex]\( \frac{13}{-1} = -13 \)[/tex]
So, [tex]\( 13 \div (-2 + 1) = -13.0 \)[/tex]
### e. [tex]\( (-36) \div (-9) \)[/tex]
To solve [tex]\( (-36) \div (-9) \)[/tex]:
- Dividing a negative number by a negative number gives a positive result.
- [tex]\( \frac{-36}{-9} = 4 \)[/tex]
So, [tex]\( (-36) \div (-9) = 4.0 \)[/tex]
### f. [tex]\( -36 \div 12 \)[/tex]
To solve [tex]\( -36 \div 12 \)[/tex]:
- Dividing a negative number by a positive number gives a negative result.
- [tex]\( \frac{-36}{12} = -3 \)[/tex]
So, [tex]\( -36 \div 12 = -3.0 \)[/tex]
### g. [tex]\( 0 \div (-12) \)[/tex]
To solve [tex]\( 0 \div (-12) \)[/tex]:
- Dividing zero by any non-zero number always gives zero.
- [tex]\( \frac{0}{-12} = 0 \)[/tex]
So, [tex]\( 0 \div (-12) = -0.0 \)[/tex]
### h. [tex]\( (-6 + 3) \div (-2 + 1) \)[/tex]
To solve [tex]\( (-6 + 3) \div (-2 + 1) \)[/tex]:
- First, solve the expressions inside the parentheses.
[tex]\( -6 + 3 = -3 \)[/tex] and [tex]\( -2 + 1 = -1 \)[/tex]
- Next, divide [tex]\( -3 \)[/tex] by [tex]\( -1 \)[/tex].
- Dividing a negative number by a negative number gives a positive result.
- [tex]\( \frac{-3}{-1} = 3 \)[/tex]
So, [tex]\( (-6 + 3) \div (-2 + 1) = 3.0 \)[/tex]
In summary:
- [tex]\( (-30) \div 10 = -3.0 \)[/tex]
- [tex]\( (-49) \div 49 = -1.0 \)[/tex]
- [tex]\( 50 \div (-5) = -10.0 \)[/tex]
- [tex]\( 13 \div (-2 + 1) = -13.0 \)[/tex]
- [tex]\( (-36) \div (-9) = 4.0 \)[/tex]
- [tex]\( -36 \div 12 = -3.0 \)[/tex]
- [tex]\( 0 \div (-12) = -0.0 \)[/tex]
- [tex]\( (-6 + 3) \div (-2 + 1) = 3.0 \)[/tex]
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.